Trend of the mortality of major liver diseases and its impact on life expectancy in China from 2006 to 2017. (18th January 2021) - Zhu, Jicun; Wang, Peng; Ye, Hua; Shi, Jianxiang; Wang, Xiao; Wang, Keyan; Duan, Fujiao; Yang, Qian; Sun, Guiying; Zhang, Jianying
Abstract: Background: Liver diseases are the serious cause of death in China. We aim to describe the trends and disparities of major liver disease mortality rates and the loss of life expectancy (LLE) in China. Methods: Annual percentage change (APC) and average APC (AAPC) were calculated using the Joinpoint regression model. LLE was calculated using cause eliminated life table. Results: From 2006 to 2017, the overall age-standardized mortality rate (ASMR) of liver cirrhosis lightly declined (AAPC: −2.97%), whereas the ASMR of viral hepatitis and liver cancer remained stable. Viral hepatitis (AAPC: −4.36%) and liver cirrhosis (AAPC: −4.35%) ASMRs both declined for females. The highest ASMRs of viral hepatitis and liver cirrhosis were in the west region, while that of liver cancer was in the middle region. The ASMRs of liver cirrhosis in the middle region and liver cancer in the east region significantly decreased. The means of LLE on viral hepatitis, liver cirrhosis and liver cancer were 0.05, 0.1 and 0.46 years, respectively. Conclusions: The burden of liver diseases is still severe and there are disparities between genders and different regions in China. Accurate early diagnostic approaches for high-risk populations should be established to eliminate the burden of liver diseases.